Literary Ethnography and Translation in Rachid Djaïdani’s Boumkoeur - Reeck, Matt (TTR)

(untitled) (Association canadienne de traductologie, 2018)
Rachid Djaïdani’s Boumkoeur (1999) exposes the inheritance of colonial anthropological thinking that dominates the reception and production of French minority literature of the banlieue. By using the ethnographic document as a textual template, Djaïdani situates his narrator, Yaz, in the space of negotiation in which colonial ethnographers and their native informants interacted in the field. Describing the French banlieue as a postcolonial ethnographic field, Djaïdani shows how Yaz as a narrator-ethnographer participates in tasks of cultural and linguistic translation. The novel directs the reader’s attention away from the production of an authentic representation of cultural difference. Instead, the novel suggests a new form of literary translation capable of abiding by translation ethics that aim to render in the target language meaningful signs of the complex cultural history of “minor” texts (Deleuze and Guattari, 1987 [1980]; Venuti, 1996) in the source language. The novel serves as an experimental literary ethnography, conceived as a new form of translation, in which the translator is an ethnographer, and the act of translation is one of linguistic and cultural translation. In this new form of translation, the translator is present in the text as an active agent. This presence makes palpable the fraught negotiations out of which any translation is born; moreover, the translator is invested with the functions of the author, adding a new literary element to the act of translation.